The dynamics of GII.4 Norovirus in Ho Chi Minh City, Vietnam. - Tra My, P; Lam, H; Thompson, C; Phuc, H; Tuyet, P; Vinh, H; Hoang, N; Minh, P; Vinh, N; Thuy, C; Nga, T; Hau, N; et al. (2013)
Norovirus (NoV) is a major cause of epidemic gastroenteritis in industrialized countries, yet the epidemiological significance of NoV in industrializing countries remains poorly understood. The spatiotemporal distribution of NoV genotypes identified in 2054 enrolled children was investigated between May 2009 and December 2010, in Ho Chi Minh City (HCMC), Vietnam. A total of 315 NoV extracted from stool samples were genotyped and GPS mapped to their source. Genogroup II NoV, particularly GII.4, were predominant, and the GII.4 strains could be subgrouped into GII.4-2006b (Minerva) and GII.4-2010 (New Orleans) variants. There was no spatiotemporal structure among the endemic GII strains; yet a significant spatiotemporal signal corresponding with the novel introduction of GII.4-2010 variant was detected. These data show that NoV GII.4 variants are highly endemic in HCMC and describe a scenario of rapid NoV strain replacement occurring in HCMC in early 2010.